The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1017/s0022112086001465
|View full text |Cite
|
Sign up to set email alerts
|

Shear-wave speeds and elastic moduli for different liquids. Part 2. Experiments

Abstract: In this paper we describe the experimental apparatus that we use to measure transit speeds. Tables of measured values of transit speeds and the corresponding values of the shear modulus are presented. The criteria we use to determine if a transit speed is a shear-wave speed are described and applied to the data. The main criteria are that transit speeds should be independent of the gap size and the corresponding value of the shear modulus should be consistent with independent rheometrical measurements. All the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 5 publications
(2 reference statements)
1
27
0
Order By: Relevance
“…We believe that our interpretation is the correct one. Support for our conviction comes from the fact that the pulse speed which we calculate in (6.20) from normal-stress differences and viscosity is of the same order of magnitude as the pulse speeds measured by Joseph et al as reported in~ [11].…”
Section: Constitulive Equation Of Joseph Et Al [12]supporting
confidence: 86%
See 1 more Smart Citation
“…We believe that our interpretation is the correct one. Support for our conviction comes from the fact that the pulse speed which we calculate in (6.20) from normal-stress differences and viscosity is of the same order of magnitude as the pulse speeds measured by Joseph et al as reported in~ [11].…”
Section: Constitulive Equation Of Joseph Et Al [12]supporting
confidence: 86%
“…We also describe the new proposition by Joseph et al [11] who have measured the speed of shear pulses and related it to their constitutive relation.…”
Section: Different Formulationsmentioning
confidence: 96%
“…The apparatus and the measuring technique are described in Joseph et al [20] and in detail in Riccius [21].…”
Section: Wave Speeds Effective Rigidity and Effective Relaxation Timesmentioning
confidence: 99%
“…He forther conjectured that the net effect was equivalent to an increase in effective viscosity and a kinetic energy damping, with an attendant reduction in velocity fluctuations and near-wall Reynolds stress. The latter conjecture is not borne out by experiment (e.g., Virk 1975), Related models are reviewed by Toonder and Nieuwstadt (1999), who also discuss an idea by Joseph et al (1986) and Joseph (1990), who argued for viscoelastic behavior and "shear waves", and conducted some experiments to look for them, Toonder and Nieuwstadt conclude that this idea ",.. is only vaguely formulated and has not been experimentally tested or theoretically elaborated,"…”
Section: Jason 2000 Drag Reductionmentioning
confidence: 99%